Food Processing from Mechanically Deboned Minced Cod - Gorbatovskiy Andrey A.; Rakityanskaya Irina L.; Kaledina Marina V. (Техника и технология пищевых производств)
Introduction. Cod is of great importance for fishing and fish processing. The main cod-based food products are frozen fish, frozen fillet, and canned cod liver. To increase the degree of processing and reduce the amount of waste, fish producers obtain minced cod from mechanically deboned leftovers of filleting. Minced fish has specific technological parameters, which limits its use in food industry. The research objective was to develop a new commercial technology of minced cod products. Study objects and methods. The research featured minced Atlantic cod. The fish was processed without thawing to reduce losses from defrosting, microbiological spoilage, and oxidation. The final product was obtained by cutting blocks of frozen minced cod on a cutter and then stabilizing the food mass with vegetable textures and food additives. The methods included selection and determination of the rheological and sensory properties of samples processed on industrial equipment. The optimal formulation was chosen according to the best results of coextruder processing. Results and discussion. Using a cutter improved the processing quality of the mechanically deboned minced cod. The samples of cold minced cod proved easier to process at a lower temperature of –7°C and below, if compared to the samples of warm minced fish (0°C and above). Adding 15% of a sunflower oil and water emulsion improved the sensory properties of finished products, e.g. fish balls in bread crumbs. Adding 4% of wheat fiber improved the texture of the products, while a higher dose made them dry and crumbly. 20% of crushed soy granules resulted in a rough texture, typical of chopped fish products. Conclusion. Rheological and organoleptic properties of highly watered mechanically deboned minced cod, as well as the texture of the finished products, could be improved by adding vegetable fillers and emulsions at a low temperature.